Diagnostic dilemmas in Fabry disease: a case series study on GLA mutations of unknown clinical significance. (5th September 2014) - Smid, B.E.; Hollak, C.E.M.; Poorthuis, B.J.H.M.; van den Bergh Weerman, M.A.; Florquin, S.; Kok, W.E.M.; Lekanne Deprez, R.H.; Timmermans, J.; Linthorst, G.E.
<x xml:space="preserve">Abstract</x> Fabry disease' (FD) phenotype is heterogeneous: alpha‐galactosidase A gene mutations (GLA) can lead to classical or non‐classical FD, or no FD. The aim of this study is to describe pitfalls in diagnosing non‐classical FD and assess the diagnostic value of plasma globotriaosylsphingosine. This is a case series study. Family 1 (p.A143T) presented with hypertrophic cardiomyopathy (HCM), absent classical FD signs, high residual alpha‐galactosidase A activity (AGAL‐A) and normal plasma globotriaosylsphingosine. Co‐segregating sarcomeric mutations were found. Cardiac biopsy excluded FD. In family 2 (p.P60L), FD was suspected after kidney biopsy in a female with chloroquine use. Males had residual AGAL‐A, no classical FD signs and minimally increased plasma globotriaosylsphingosine, indicating that p.P60L is most likely non‐pathogenic. Non‐specific complications and histology can be explained by chloroquine and alternative causes. Males of two unrelated families (p.R112H) show AGAL‐A <5%, but slightly elevated plasma globotriaosylsphingosine (1.2–2.0 classical males >50 nmol/l). Histological evidence suggests a variable penetrance of this mutation. Patients with GLA mutations and non‐specific findings such as HCM may have non‐classical FD or no FD. Other (genetic) causes of FD‐like findings should be excluded, including medication inducing FD‐like storage. Plasma globotriaosylsphingosine may serve as a diagnostic tool, but histology of an affected organ is often mandatory.